Analysis of Defuzzification Method for Rainfall Event - Uraon, Kiran Kumar; Kumar, Shiv (IJRDO -Journal of Computer Science Engineering, 2016)
Fuzzy Logic is present trend for decision making, classification and predictionwhere problem can be formulated by mapping input variable with output variable or wheresimple solution does not exists. There are three basic steps for fuzzy inference system such asFuzzification, rule evaluation and Defuzzification. Fuzzification means converting numeric valueinto linguistic value. Human intuition method is well accepted method for the membershipfunction value assignment throughout the world. Fuzzy inference engine produce the result afterrule evaluation also in terms of linguistic value. All results are aggregated and defuzzified by anyDefuzzification method. It is very difficult to know which process will be suitable for which typeof data.So, the main objective of this paper is to explore the basic concept of Defuzzification method forthe rain fall event with the help of wind speed and temperature variable by simulating on matlabanalyze the obtained results for different-different fuzzyfication methods the rain fall event in“MatLab”.